Use of nested PCR for the detection of trichomonads in bronchoalveolar lavage fluid - Lin, Chao (BMC Infect Dis, 2019)
BACKGROUND: The methods routinely used to detect trichomonads in the lungs are not sensitive enough, and an effective method is urgently needed. METHOD: Primers were first designed to match the conserved area of the 18S rRNA gene of trichomonads. Then, nested PCR was carried out to detect trichomonads in bronchoalveolar lavage fluid (BALF). Finally, all positive specimens were subjected to DNA sequencing and phylogenetic analysis. RESULTS: Among 115 bronchoalveolar lavage fluid samples, ten samples tested positive in nested PCR (10/115), while no samples were positive in wet mount microscopy (0/115) (P < 0.01). Among the ten positive specimens, two were identified as Tetratrichomonas spp. and the other eight as Trichomonas tenax in phylogenetic analysis. CONCLUSIONS: Nested PCR is an effective way to detect trichomonads in bronchoalveolar lavage fluid.